Multiliteration and Higher Order Thinking Skills Implications to Education - Tatang Syaripudin (Universitas Sebelas Maret, 2019)
This paper aims to describe multiliteration and higher order thinking skills (HOTS) as challenges for 21st century society, as well as their implications to education. 21st century civilization has triggered the development of the meaning of literacy into multiliteration, and requires the public to have cognitive process skills that are classified as higher order thinking skills. Based on analysis of implications, multiliteration and higher order ranking skills have implications to education. Especially in developing thinking process skills, the purpose of education should be directed at developing cognitive process skills at levels C2 through C6. The curriculum is ideally holistic, integrative, child centered and activity centered. The learning approach is student-centered and applies heuristic strategies. In its implementation, it is necessary to apply various models and/or learning methods that require students to do problem solving, think creatively, and cooperate. The teacher acts as a guide and facilitator rather than as an instructor. 21st century teachers ideally have characteristics: permissive, friendly, a guide, open-minded, enthusiastic, creative, socially aware, alert, patient, cooperative and sincere.